2010
DOI: 10.1182/blood.v116.21.2071.2071
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Csda Protein Complexes Involved In Modulation of Fetal Globin Gene Expression

Abstract: 2071 Impaired switching from fetal hemoglobin (HbF) to adult globin gene expression leads to hereditary persistence of fetal hemoglobin (HPFH) in adult life. This is of prime interest because elevated HbF levels ameliorate beta-thalassemia and sickle cell anemia. Fetal hemoglobin levels are regulated by complex mechanisms involving factors linked or not to the beta-globin gene locus. Recently, we reported an inverse relationship between Ggamma-globin gene (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, chromatin immunoprecipitation (ChiP) analysis in K562 cells showed that CSDA interacts with this promoter region, thus confirming that CSDA modulates HBG expression at the transcriptional level [18]. Subsequently, it has been proposed that NF-kB and histone deacethylase 2 (HDAC2) interact with CSDA to form a multiprotein complex which take part to the regulation of HBG2 expression by modulating local chromatin conformation [23], thus highlighting the relevance of the role played by CSDA in fetal globin gene expression and shedding novel light on the molecular mechanisms involved in globin gene switching (Figure 3).…”
Section: Cold-shock Domain Protein a (Csda)mentioning
confidence: 82%
See 1 more Smart Citation
“…Also, chromatin immunoprecipitation (ChiP) analysis in K562 cells showed that CSDA interacts with this promoter region, thus confirming that CSDA modulates HBG expression at the transcriptional level [18]. Subsequently, it has been proposed that NF-kB and histone deacethylase 2 (HDAC2) interact with CSDA to form a multiprotein complex which take part to the regulation of HBG2 expression by modulating local chromatin conformation [23], thus highlighting the relevance of the role played by CSDA in fetal globin gene expression and shedding novel light on the molecular mechanisms involved in globin gene switching (Figure 3).…”
Section: Cold-shock Domain Protein a (Csda)mentioning
confidence: 82%
“…In the last years, many efforts have been aimed at clarifying the repression mechanism exerted by BCL11A at the HBB locus. At this regard, an important contribution has been provided by the identification of the multiprotein complex Transcriptional repressor mechanisms of fetal globin genes in adult erythropoiesis involving BCL11A and CSDA multiprotein complexes [23][24][25][26][27].…”
Section: B-cell Lymphoma/leukemia 11a (Bcl11a)mentioning
confidence: 99%